Efektifitas Penggunaan Google Workspace Untuk Pembelajaran Daring Menggunakan Model Delone-Mclean Dan PLS-SEM - Indzaldi Gianjas Saputra; Ersi Destiani; Eni Heni Hermaliani; Riyan Latifahul Hasanah (Universitas Bina Sarana Informatika Kota Sukabumi, 2022)
The learning system at Tri Arga 2 Jakarta Vocational School has implemented online learning by using Google workspace, especially Google classroom as a learning medium. The problems that occur are obstacles during the learning process, such as the lack of students' understanding of the learning material provided and inadequate signals. The purpose of this study was to analyze the effectiveness of the use of google workspace using the Delone-Mclean and PLS-SEM methods as well as distributing questionnaires to a sample of Tri Arga 2 Vocational High School students in Jakarta. While the research method by applying quantitative methods with a case study approach. The results of the analysis conclude that the use of the Delone-Mclean model in an online learning system with google workspace, has a success percentage value of 37.67%. While the results of the analysis using the PLS-SEM model which was tested using SmartPLS 3.0 software, which has a significant influence with a success rate of 95% and a failure rate of 5%. The software used to analyze the questionnaire data is SPSS 25 and SmartPLS 3.0. It can be said that the results of the analysis of system success using the two methods of Delone-Mclean and PLS-SEM have quite a large difference.